How to be a good creature - Montgomery, Sy (Houghton Mifflin Harcourt, 2018)
The author presents the story of her life by reflecting on the personalities and quirks of thirteen different animals she's encountered in her life and travels as an author, naturalist, and adventurer. Includes resources for further information and photographs.